Monitoring of severe traumatic brain injuries in the neurointensive care unit - Rintala, Aaron (My University, 2024)
The purpose of this review was to provide an overview of the recent studies discussing the current state of multimodality monitoring (MMM) of severe traumatic brain injury (sTBI) using both invasive and non-invasive techniques in neurointensive care. In addition, the latest randomized controlled trials RCTs on decompressive craniectomy (DC) for the management of refractory post-traumatic intracranial hypertension will be discussed. A literature search was performed in PubMed, Scopus, Google Scholar and ISI Web of Knowledge for articles in English. The search included recent guidelines, meta- analyses, observational studies, RCTs, systematic and narrative reviews. MMM, specifically, intracranial pressure (ICP) monitoring, brain tissue oxygen tension, pressure reactivity index, and cerebral microdialysis, are a promising group of techniques for understanding the complex pathophysiology following TBI. Invasive ICP monitoring is widely regarded as the most critical modality for the treatment of sTBI. Regarding non-invasive monitoring, optic nerve sheath diameter, near-infrared spectrometry and transcranial doppler have shown promising results. S100B could serve as a tool for MMM. In case of intractable ICP after failed maximal medical therapy, secondary DC should be considered as a life-saving option and should be made on a case-by-case basis. We conclude that in isolation, no monitoring tool is likely to change outcomes, but when used as part of a goal-directed therapeutic strategy it could hypothetically influence outcomes. Critical care practitioners need to understand that these tools should be used in an integrated fashion, combining MMM data with the clinical examination, systemic monitoring, neuroimaging, and additional specialized monitoring tools.
Keywords: traumatic brain injury, multimodality monitoring, intracranial pressure, decompressive craniectomy